Levelling-up rhodolith-bed science to address global-scale conservation challenges - Tuya, Fernando (2023)
Global marine conservation remains fractured by an imbalance in research efforts and policy actions, limiting progression towards sustainability. Rhodolith beds represent a prime example, as they have ecological importance on a global scale, provide a wealth of ecosystem functions and services, including biodiversity provision and potential climate change mit- igation, but remain disproportionately understudied, compared to other coastal ecosystems (tropical coral reefs, kelp for- ests, mangroves, seagrasses). Although rhodolith beds have gained some recognition, as important and sensitive habitats at national/regional levels during the last decade, there is still a notable lack of information and, consequently, specific conservation efforts. We argue that the lack of information about these habitats, and the significant ecosystem services they provide, is hindering the development of effective conservation measures and limiting wider marine conservation success. This is becoming a pressing issue, considering the multiple severe pressures and threats these habitats are exposed to (e.g., pollution, fishing activities, climate change), which may lead to an erosion of their ecological function and eco- system services. By synthesizing the current knowledge, we provide arguments to highlight the importance and urgency of levelling-up research efforts focused on rhodolith beds, combating rhodolith bed degradation and avoiding the loss of associated biodiversity, thus ensuring the sustainability of future conservation programs.